National immunisation days in Bangladesh: an evaluation of the 1996 rounds - Karim, Fazlul; Chowdhury, AMR; Bhuiya, Abbas; Aziz, KMA; Ali, Ahmed; Islam, Md. Nazrul; Mahmud, Shah Noor; Mol, Dineke (BRAC Research and Evaluation Division (RED), 2019)
On April 16 and May 16 .1996, Bangladesh implemented the third and fourth of the six National Immunization Days. On those days oral polio vaccine (OPV) was administered to over 20 million children under 5 years of age. The goal of NIOs is to eradicate poliomyelitis from the country by 2000 AD. NID is a challenging campaign for Bangladesh mobilising a huge human and material resources. This study examined how effective NIDs are in terms of implementation and coverage of the target children and what lessons can be learned from it. The study was implemented as a part of the multi-country 'Social Science and Immunisation' project".